Math

posted by .

How would I solve the quadratic equation: 2x^2 + 6x = 0



I would factor out 2x to give
2(x+3)=0

2x^2 = -6x;

2x = -6;

x = -3.

hopefully thts the answer!

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math

    how would you solve for y in this problem: x=(y^2+3y)^(1/3) would it equal: y= x^3/y - 3 ?
  2. math,algebra

    can someone help me out factor out this 0=16t^2-122t+180 i have so far this but the last one i am not sure 8(2t^2-14t + ?
  3. Liberal Arts Math

    how would i solve this problem?? it says factor the polynomial completely: 2xy-3y-40x+60 I studied polynomials, but I don't know what it means to factor them. Do you have a definition in your textbook or notes or something?
  4. algebra

    It is not solvable by that method, shanaid. You have to get all the numbers on the left, set them to equal zero, and factor. which method is used to solve this equation. x^2-9x-4=6 I would factor, move the six over, then factor i would …
  5. math

    The "x intercept" is where y = 0, which is where the curve crosses the x axis. Solve y = x^2+ 2x- 8 = 0 You can write that as y = (x+4) (x-2) = 0 There are two places where y = 0. The factored equation tells you where they are. how …
  6. math

    solve the equation x^3-5x^2-4x+20=0 I need a hint on how to solve this Look for the first root by graphical means or trial-and-error. Note that when x=2, x^3-5x^2-4x+20 = 8-20 -8 +20 = 0. Therefore 2 is one root and x-2 is a factor. …
  7. Math

    -x^3 + 1.85x^2 - x +0.15 = 0 how can you solve for x?
  8. algebra

    1)Solve by factoring:5x^2=4-19x answer=-4,1/5 2)Which quadratic equation has roots 7 and -2/3?
  9. Math

    Can 2xy - y - 1 be factored out? How? about all you can do is take the common y out of the first two terms; that in itself is not much help. dont know if this is rite or not..but just a guess.. assuming 2xy - y - 1 = 0 2xy - y = 1
  10. advanced math

    Hi, I am trying to solve graphing quadratic equations. One of the problems is written as -x^2= -2x-1. So if I wanted to put this equation in the proper quadratic equation form, would it be -2x-1-x^2, or -x^2+-2x-1?

More Similar Questions